Effectiveness of Mental Basic Course Training Health Nursing on the Ability of Nurse to Carry Out Mental Nursing Care - Nofrida nofi saswati; Isti Harkomah (NurseLine Journal, 2021)
Problems that occur in clients with mental disorders are not obedient to taking medication, where clients who have finished undergoing treatment at the Mental Hospital are returned to their families but the obstacles found are that the role of nurses who hold mental health programs is not optimal in carrying out mental nursing care in either community for the nursing diagnosis of mental, psychosocial and mental health disorders. Therefore it requires a family role related to treatment and care for clients with mental disorders. One of the programs to stimulate the role of the family towards clients with mental disorders is the training of CMHN (Community Mental Health Nursing) nurses. The research objective was to determine the effect of BC-CMHN training on the self-ability of nurses in implementing community mental nursing care in Jambi City. This research is a quasi experimental design with a pretest-posttest one group design. Respondents in this study were 20 puskesmas nurses who are responsible for mental health programs. Based on the results of the bivariate analysis using the dependent t-test that cognitive abilities before and after the intervention (p = 0.000). There is an effect of BC-CMHN training on the self-efficacy of nurses in implementing community mental health insurance in Jambi City, it is recommended that it be implemented at both the provincial and district / city levels to improve the quality of community mental health service.s